EVALUATION OF CHARACTER EDUCATION PROGRAMS - Efitri LESTARI (Journal of Education and Leadership in Education, 2022)
This research is an evaluation research which aims to find, prove, and analyze the success of the character education program in Madrasah Ibtidaiyah Az Zarofah Jakarta Timur. This research uses the CIPP evalutaion model, which stands for Context, Input, Process, and Product. The research method uses a qualitative approach, namely by obtaining scientific data including data collection carried out through observation, interviews, and documentation techniques. The subject in this research of the headmaster, student field, curriculum field, student guardian, teacher, treasurer or head of administration, students, and alumni. Then the data are analyzed by reduction, presentation and drawing conclusions. Based on the research conducted, the following results were obtained: 1) The context aspect is divided into three components of evaluation, namely, philosophical foundations, vision and mission and program objectives, as well as program urgency. The analysis of the three aspects can be concluded to have high actuality. 2) In the input aspect consisting of the curriculum, the competence of the principal, the character of teachers, students, financing, and parental support, it's just that the facilities and infrastructure need to be improved. 3) In the process aspect, learning is well designed starting from learning activities, extracurricular activities, and supervision. 4) In the product aspect, which consists of internalizing character values, academic impact and non-academic impact has high actuality. This shows that students are able to apply character values well, have a positive impact on academic achievement, and have a positive impact on non-academics, namely daily behavior.